Project-Based Learning on Hydroponic Vegetable Cultivation Affecting Collaboration Skills and Academic Achievement among Grade 11 Students - Boonyassa, Manida; Wongsaphan, Montree (ARU Research Journal Humanities and Social Sciences, 2026)
This research aimed to 1) develop an effective project-based learning plan on hydroponic vegetable cultivation for 5th-grade students, meeting the 80/80 efficiency criterion; 2) compare the collaborative skills of 5th-grade students after the learning plan with the 80% criterion; 3) compare the academic achievement of 5th-grade students after the learning plan with the 80% criterion; and 4) study the satisfaction of students with the project-based learning plan on hydroponic vegetable cultivation. The sample consisted of 32 5th-grade students from class 5/3 at Nachuk Pittayasarn School, under the Mahasarakham Secondary Educational Service Area Office, during the second semester of the 2025 academic year. The sample was obtained through cluster sampling using the classroom as the sampling unit. The research instruments included: 1) Seven project-based learning lesson plans; 2) A collaborative skills assessment form with four indicators; 3) A 30-item multiple-choice achievement test with four options; and 4) A 15-item five-level Likert scale student satisfaction questionnaire. The statistical methods used were mean, standard deviation, percentage, and a one-sample t-test. The research findings revealed that: 1) The project-based learning plan on hydroponic vegetable cultivation was effective, achieving scores of 81.14/84.62, exceeding the set criterion of 80/80. 2) The collaborative skills of 5th-grade students after project-based learning significantly exceeded 80%, a statistical significance level of .01. 3) The post-test academic achievement scores of 5th-grade students were significantly higher than 80%, with a statistical significance level of .01; and 4) The satisfaction level of 5th-grade students after project-based learning was at the highest level. (x ̅=4.52, S.D.=0.65)